Chemical Characteristics of Legen Drinks from Street Vendors in Surabaya - SARTIKA, LUTFITA DEWI; Yulistiani, Ratna (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Legen is a traditional drink made of siwalan sap and it is very popular in East Java. This research aims to identify chemical characteristics of legen drinks sold by 10 local street vendors in Surabaya. This study is an exploratory and descriptive survey employing a cross-sectional approach. Data were collected by observation, interviews, and questionnaires regarding vendor characteristics, involving 10 street vendors selling legen drinks in Surabaya who operate throughout the year. The observed parameters include pH, total sugar, total acidity, and alcohol content. The observations showed that the vendors were predominantly male (90%), with the remaining 10% is female. The vendors’ ages ranged from 26 to 55 years, with most having completed junior high school (40%) and senior high school (40%). Only one vendor had been selling for more than 20 years. The selling price of the product ranged from IDR 13,000 to 15,000 per 1,500 mL bottle, with most of the legen (80%) sourced from Tuban. The chemical analysis showed that the average pH was 2.85, the average total acidity was 0.22, the average total sugar content was 10.60, and the average alcohol content was 1.02. Contribution to Sustainable Development Goals (SDGs):SDG 3 – Good Health and Well-beingSDG 8 – Decent Work and Economic GrowthSDG 11 – Sustainable Cities and CommunitiesSDG 12 – Responsible Consumption and Production